2007
DOI: 10.1016/j.marenvres.2007.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and seasonal variations of algal toxins in water, phytoplankton and shellfish from North Stradbroke Island, Queensland, Australia

Abstract: A number of marine microalgae are known to produce toxins that can accumulate in shellfish and when eaten, lead to toxic and potentially fatal reactions in humans. This paper reports on the occurrence and seasonal variations of algal toxins in the waters, phytoplankton and shellfish of Southeast Queensland, Australia. These algal toxins include okadaic acid (OA), domoic acid (DA), gymnodimine (GD), pectenotoxin-2 (PTX-2) and pectenotoxin-2-seco acid (PTX-2-SA), which were detected in the sampled shellfish and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…We have demonstrated the successful application of HP20 for detection of the hydrophilic toxins DA and PST in the field, and previous studies have demonstrated its applicability for lipophilic toxins (Fux et al 2009;Fux et al 2008;Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007;Turrell et al 2007). HP20 demonstrates characteristics that perhaps most closely imitate those of a mussel, i.e., a relatively low rate of accumulation (19% over 7 d) and a relatively higher rate of desorption.…”
Section: ; Aoac International 2006)mentioning
confidence: 68%
See 2 more Smart Citations
“…We have demonstrated the successful application of HP20 for detection of the hydrophilic toxins DA and PST in the field, and previous studies have demonstrated its applicability for lipophilic toxins (Fux et al 2009;Fux et al 2008;Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007;Turrell et al 2007). HP20 demonstrates characteristics that perhaps most closely imitate those of a mussel, i.e., a relatively low rate of accumulation (19% over 7 d) and a relatively higher rate of desorption.…”
Section: ; Aoac International 2006)mentioning
confidence: 68%
“…Extraction of a field SPATT sample is comparatively lower in time and labor requirements. The SPATT extraction described here includes a three-step series of column elutions that can be completed within 10-30 min, yielding extracts that are available for immediate analysis of a single toxin or of multiple toxins, as demonstrated (e.g., DA or DA plus PST), We note that others have already demonstrated the ability to use HP20 for a suite of marine toxins (Fux et al 2008(Fux et al , 2009Mackenzie et al 2004;Pizarro et al 2008aPizarro et al , 2008bRundberget et al 2007Rundberget et al , 2009Takahashi et al 2007). The resin and extract are reasonably stable when stored at -80°C, providing the ability to archive samples for further analysis at a later time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that correlation between Pseudonitzschia abundance and pDA concentration is not significant when the study area does not have sufficient water circulations (Takahashi et al, 2007;Schnetzer et al, 2007;Bargu et al, 2012). In the sampling area, if we consider the water circulations at stations FD5 and FD6, it is possible to say that unsuitable environmental conditions at the section UE may limit the growth of Pseudo-nitzschia species and also their toxin production.…”
Section: Discussionmentioning
confidence: 96%
“…Since their discovery in the early 1990s in New Zealand [2] and Canada [5], gymnodimines and spirolides have been demonstrated to have a global distribution. GYMs have been also detected in Tunisia [6] and Australia [7] Abbreviations: nAChR, nicotinic acetylcholine receptor; BSA, bovine serum albumin; ␣-BTX, ␣-bungarotoxin; FP, fluorescence polarization; GYM, gymnodimine; PBS, phosphate buffered saline; SPX, spirolide.…”
Section: Introductionmentioning
confidence: 99%